Civil Responsibility in Surrogacy - H Rahimi (JRI, 2008)
Introduction: One of the methods used for the management of human infertility is using another woman’s uterus called a surrogate uterus or a rented womb which can be in full or partial modes. In full surrogacy, we do not use the gametes of the bearer woman but in the partial surrogacy we do. Materials & Methods: In this article we will study civil responsibilities in full surrogacy. In other words, we aim to answer the question that in what conditions one is responsible for the damages of another person while on full surrogacy. We use civil responsibility in its broad sense, including contract responsibility and tort. Since there are no special regulations for surrogacy in the Iranian Law, we will refer to general rules, Islamic Jurisprudence (Fiqh) and the laws of other countries to find the best solution for the problems. Results: For the validity of surrogacy contract, it is not enough to observe article 10 of the civil code or the general rules of contract laws but it is necessary to ratify specifically addressed laws. In the mean time, the couples who want the child and the bearer and her husband (if she is married) must negotiate about all the issues and obligations so that the limitations and responsibilities of the two parties are reflected in the contract completely. On non-contract responsibilities, there is either no valid contract at all between the bearer of the damages and the person who is deemed responsible or there is no relation between the damages occurred and the breach of the contractual obligations but there is a breach of general duties and customs instead. The regulations relating to civil responsibility are broad enough to include our subject too. As the surrogacy subject is rather new and customs have not been developed accordingly, problems are likely to arise where one can not determine the moment that faults occur. Conclusion: It seems that the Iranian Parliament should intervene and ratify certain laws and regula-tions for surrogacy, as surrogacy might have some social consequences with resultant problems if ignored or not addressed legally.
Keywords: Surrogacy, Surrogate Mother, Uterus, Rented womb, Civil responsibility, Contractual responsibility, Tort, Non-Contractual responsibility